Prove by mathematical induction that the formula found in the previous problem is valid. First, outline the proof by clicking and dragging to complete each statement.1.Let P(n) be the proposition that2.Basis Step: P(0) and P(1) state that3.Inductive Step: Assume that4.Show that5.We have completed the basis stepand the inductive step. By mathematical induction, we know thatSecond, click and drag expressions to fill in the details of showing that ∀ k(P(1) ∧ P(2) ∧ ... ∧ P(k) → P(k + 1)) is true, thereby completing the induction step.==IH==